UTILIZING GADGET BASED INTERNET APPROACH DURING THE PANDEMIC TO IMPROVE STUDENTS’ BAHASA INDONESIA LEARNING OUTCOMES AT GRADE IV OF SD NEGERI 10 BAGAN PUNAK KECAMATAN BANGKO - Dahniar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to improve the learning outcomes of fourth-grade students at SDN 010 Bagan Punak, Kecamatan Bangko, through a gadget-based internet use approach. The subjects of this study consisted of 20 students, and the research was conducted using classroom action research to enhance both learning outcomes and learning activities. The initial average score of students’ learning outcomes was 60, indicating that the learning completeness had not been achieved. After implementing gadget-based internet learning using Zoom media from cycle I to cycle II, students’ learning outcomes increased progressively. In the first cycle, the average score rose to 74.6, with 15 out of 20 students (75%) reaching complete learning outcomes. In the second cycle, the average score further increased to 81.8, with 18 students (90%) achieving completeness, demonstrating the effectiveness of using internet-based learning in improving students’ learning outcomes in Bahasa Indonesia.